Arrays of liquid crystal lenses based on photosensitive polymer orientant - Stanevich, Veranika Yu.; Chepeleva, Daminika S.; Kurilov, Alexander D.; Bezruchenko, Veronika S.; Murauski, Anatoli A. (Journal of the Belarusian State University. Physics, 2023)
New approaches have been developed for creating liquid crystal devices that control the angular distribution of light. An alignment material has been synthesised, with help of which the distribution of the liquid crystal director on the surface of the substrates is formed. When light passes through the liquid crystal cell, distribution makes possible to obtain a wave front similar to a conventional lens. This material is a copolymer (BVS) of butyl methacrylate (BMA), vanillyl methacrylate (VMA) and stearyl methacrylate (SMA). Liquid crystal cells with different lens array packages (square and hexagonal) are manufactured. It is shown that in order to realise the maximum scattering of a controlled refractive-scattering structure, the lens density in the packing should be as high as possible. It has been established that the hexagonal packing of the lens array is optimal, since in this case the area occupied by the lenses is 5 % larger than in the case of square packing. The focal length of an array of liquid crystal lenses in polarised light is calculated. It has been established that the smallest focal length is typical for the blue wavelength range, and the largest for the red one. The dependence of the focal length on the radius of the liquid crystal lens, the thickness of the liquid crystal layer and the birefringence of liquid crystal materials is studied. The developed copolymer (BVS) makes it possible to manufacture an array of lenses on a plastic substrate due to low-temperature processing (≤ 70 °C), which leads to the prospects for using this material in the field of creating modern devices and systems for controlling light beams.
Keywords: liquid crystal; copolymer; aligning materials; liquid crystal lenses; lens array